RAPD-PCR characterisation of two Enterococcus lactis strains and their potential on Listeria monocytogenes growth behaviour in stored chicken breast meats: Generalised linear mixed-effects approaches. (January 2019) - Ben Braïek, Olfa; Smaoui, Slim; Ennouri, Karim; Morandi, Stefano; Cremonesi, Paola; Hani, Khaled; Ghrairi, Taoufik
Abstract: This study deals with the genetic characterisation of two enterocin-producing Enterococcus lactis strains named Q1 and 4CP3 using Randomly Amplified Polymorphic DNA (RAPD)PCR and the effect of their separate additions in the control of Listeria monocytogenes in refrigerated chicken breast meat. These strains demonstrated interesting in vitro antimicrobial activity towards L. monocytogenes EGDe 107776 by agar assay. To evaluate the in situ effect of E. lactis strains against L. monocytogenes in white meat model, chicken breast were artificially contaminated with 10 5  CFU/g of L. monocytogenes and inoculated with E. lactis Q1 and 4CP3 of each at 10 7  CFU/g. The pathogen counts were monitored during cold storage for 28 days. The anti-listerial effect of the enterococcal cultures was examined using linear (ANOVA) and general (ANCOVA) models and it has been shown that both of them controlled L. monocytogenes by decreasing ( P  < 0.05) and suppressing the pathogen growth in refrigerated chicken meats during 28 days of storage. The present study shows that our E. lactis strains have great potential as protective cultures and might be used for preventing the growth of pathogenic bacteria such as L. monocytogenes in meat products during their refrigerated storage. Highlights: Enterococcus lactis Q1 and 4CP3 strains produce enterocins A, B and/or P. Enterococcus lactis Q1 and 4CP3 strains were characterised genetically by RAPD-PCR. Assessment of anti-listerial activity in chicken meat by linear and general models. Q1 and 4CP3 significantly inhibit the Listeria monocytogenes growth in chicken meat. Q1 and 4CP3 strains are considered as potent protective cultures in food safety.